A new auroral phenomenon, the anti-black aurora - Nel, A.E.; Kosch, M.J.; Keith Whiter, Daniel; Gustavsson, Björn Johan; Aslaksen, Torun Helene (Scientific Reports, 2021)
Black auroras are small-scale features embedded in the diffuse background aurora, typically occurring post-substorm after magnetic midnight and with an eastward drift imposed. Black auroras show a significant reduction in optical brightness compared to the surrounding diffuse aurora, and can appear as slow-moving arcs or rapidly-moving patches and arc segments. We report, for the first time, an even more elusive small-scale optical structure that has always been observed occurring paired with ∼ 10% of black aurora patches. A patch or arc segment of enhanced luminosity, distinctly brighter than the diffuse background, which we name the anti-black aurora, may appear adjacent to the black aurora. The anti-black aurora is of similar shape and size, and always moves in parallel to the drifting black aurora, although it may suddenly switch sides for no apparent reason. The paired phenomenon always drifts with the same average speed in an easterly direction. From the first dual-wavelength (427.8 nm and 844.6 nm) optical observations of the phenomenon recorded on 12 March 2016 outside Tromsø Norway, we show that the anti-black and black auroras have a higher and lower mean energy, respectively, of the precipitating electrons compared to the diffuse background.